Effect of Inclusion of Degraded and Non-Degraded Date Pits in Broilers’ Diet on their Intestinal Microbiota and Growth Performance - Salem R. Alyileili; Ibrahim E. H. Belal; Ahmed S. Hussein; Khaled A. El-Tarabily (Animals, 2020)
The current study aims to assess the effect of non-degraded date pits (NDDP) and degraded date pits (DDP) in broilers’ diets on gut microbiota and growth performance. The degradation of date pits (DP) occurred via the cellulolytic fungus Trichoderma reesei by a solid-state degradation procedure. One-day-old Brazilian broilers were allocated into six dietary groups: (1) maize–soy diet, (2) maize–soy diet with oxytetracycline (20%, 50 g 100 kg−1), (3) maize–soy diet with 5% NDDP, (4) maize–soy diet with 10% NDDP, (5) maize–soy diet with 5% DDP, and (6) maize–soy diet with 10% DDP. At the end of the trial, the total count of bacteria was significantly (p < 0.05) less in broilers fed 10% DDP diet (treatment 6) compared with the control group (treatment 1). In addition, DDP and oxytetracycline control diets have a similar diminishing effect on total bacterial counts and the populations of Salmonella, Campylobacter, Shigella spp., and Escherichia coli. Over 35 days of trial, weight gains were similar among the six dietary groups. Our results showed that DDP and control diets have a similar effect on growth performance. The feed conversion ratio (FCR) was poorer in broilers fed NDDP diets than other treatments. The European Production Efficiency Index (EPEI) was greater with 5% and 10% DDP than those fed NDDP at the same levels, with no significant variance from the control and antibiotic-supplemented diet (treatment 2). Overall, it can be suggested that maintaining 10% of DDP can partly replace dietary maize while also serves as a gut health enhancer and thus a growth promoter in the diet for broilers.